Life Cycle Assessment of Green Diesel Production by Hydrodeoxygenation of Palm Oil - Arguelles-Arguelles, Antonio; Amezcua-Allieri, Myriam Adela; Ramírez-Verduzco, Luis Felipe (Frontiers in Energy Research, 2021)
Transition to a new energy low carbon pool requires the gradual replacing of fossil fuels with other cleaner energies and biofuels. In this work, the environmental impact of renewable diesel production using an attributional life cycle assessment was evaluated by considering five stages: palm plantation-culture-harvest, palm oil extraction, palm oil refining, green (renewable) diesel production, and biofuel use. The functional unit was established as 1.6 × 10−2 m3 (13.13 kg) of renewable diesel. The results show that the production of renewable diesel by Hydro-processed Esters and Fatty Acids is more environmentally friendly than fossil diesel production. In particular, the analysis showed that the CO2 emission decreases around 110% (i.e. mitigation occurred) compared with conventional diesel production. However, renewable diesel production has a relevant environmental impact in the human toxicity category due to the high consumption of agrochemicals during palm culture.